2017
DOI: 10.1002/bio.3271
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence‐based sensor for selective and sensitive detection of amoxicillin (Amox) in aqueous medium: Application to pharmaceutical and biomedical analysis

Abstract: We here for the first time demonstrate an analytical approach for the highly selective and sensitive detection of amoxicillin (Amox) in aqueous medium based on the fluorescence quenching of quantum dots (QDs). The change in fluorescence intensity of mercaptopropionic acid-capped cadmium sulphide (MPA-CdS) QDs is attributed to the increasing concentration of Amox. The results show that the fluorescence quenching of QDs by Amox takes place through both static and dynamic types of quenching mechanism. The fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…S. P. Pawar et al . demonstrated AMX determination method based on the fluorescence quenching of quantum dots (QDs). The developed method has been successfully applied for the determination of amoxicillin in pharmaceutical formulations and urine samples with acceptable results.…”
Section: Introductionsupporting
confidence: 89%
“…S. P. Pawar et al . demonstrated AMX determination method based on the fluorescence quenching of quantum dots (QDs). The developed method has been successfully applied for the determination of amoxicillin in pharmaceutical formulations and urine samples with acceptable results.…”
Section: Introductionsupporting
confidence: 89%
“…25−27 Innovative combinations of known components may lead to the development of multifunctional materials that provides superior composite material with possible applications in various fields such as catalysis, electronics, biosensing, drug delivery, nanomedicine, and environmental remediation, to name a few. 28 Until now, many reports used carbon dots in aqueous medium; however incorporating them into a gel matrix offers rigidity and stability that results in the outstanding properties of hybrid material. Cayuela et al reported the mixing of functionalized carbon nanodots into a low molecular weight salt hydrogel that exhibited a sensor response toward Pb 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pawar et al synthesized mercaptopropionic acid‐capped (MPA) cadmium sulfide (CdS) QDs and used the fluorescence quenching of the QD method to detect AMX in pharmaceutical formulations and urine samples. [ 41 ] The change in fluorescence intensity of QDs was recognized by the cumulative concentration of AMX. The obtained results confirmed that the fluorescence quenching of QDs showed a linear response with the AMX concentration.…”
Section: Optical Sensors For Amx Detectionmentioning
confidence: 99%